Treatment principles of children with pharyngeal tonsil pathology in the background of allergic rhinitis (literature review): A review - Yulya E. Orlova; Valery M. Svistushkin; Galina N. Nikiforova; Elena A. Shevchik (Consilium Medicum, 2022)
This article provides a review of different treatment for children with adenoids against a background of allergic rhinitis. An analysis of 35 papers published in Scopus and PubMed was carried out. Evaluation of the research results has shown that treatment of patients with pathology of lymphoid structures of the pharynx on the background of allergic rhinitis should be complex and individual in each clinical case.